TRPM1 (melastatin) expression is an independent predictor of overall survival in clinical AJCC stage I and II melanoma patients. (26th January 2017) - Brożyna, Anna A.; Guo, Huazhang; Yang, Sun‐Eun; Cornelius, Lynn; Linette, Gerald; Murphy, Michael; Sheehan, Christine; Ross, Jeffrey; Slominski, Andrzej; Carlson, J. Andrew
Abstract : Background: The expression of TRPM1 (melastatin) mRNA is an independent marker, as measured by radioactive in situ hybridization (RISH), of disease‐free survival in primary cutaneous melanoma (PM). The aim of the study was to determine if chromogenic in situ hybridization (CISH) can reproduce results examining diagnostic and prognostic utility of TRPM1 mRNA expression in melanocytic proliferations as measured by RISH. Methods: The expression of TRPM1 mRNA was detected by CISH in melanocytic nevi (MN, n  = 61), PM ( n  = 145) and metastatic melanomas (MMs, n  = 15). Results: A progressive loss of TRPM1 was found moving from MN to PM to MM. The histologic stepwise model of melanoma progression revealed that loss of TRPM1 occurred at the transition of RGP PM to VGP PM. As a diagnostic marker, TRPM1 gradient loss showed 93.8% sensitivity and 52.4% specificity for PM. Loss of TRPM1 mRNA correlated with melanoma aggressiveness markers and was independent predictor of disease‐free and overall survival. The corresponding survival curves for degree of melanoma pigmentation matched those for degree of loss of TPRM1 mRNA. Conclusion: Loss of TRPM1 mRNA expression appears to be a crucial event in the progression of melanoma to a more malignant, metastatic phenotype.